Monte Carlo Simulation and N-XCOM Software Calculation of the Neutron Shielding Parameters for the NCRP Report 144 Recommended Conventional Concretes - Makkiabadi, Nahid; Ghiasi, Hosein (Frontiers in biomedical technologies, 2024)
Purpose: Radiation shielding requires deep knowledge about the shielding materials properties. Additionally, the interaction between the radiation and materials should be well understood. Materials and Methods: Monte Carlo (MC) simulation, NXCOM, and WinXCOM computational programs were utilized for the concrete shielding properties against 1.5 MeV neutron beam and 137Cs emitted γ-ray. In a simulated “good geometry” using MCNP5 MC code, NXCOM and WinXCOM, radiation attenuation factor (µ), microscopic neutron removal cross-section (  Half and Tenth Value Layers (HVL and TVL) of the studied concretes were derived. Obtained results by the methods were compared and discussed. Results: For 137Cs emitted γ-ray, mass attenuation factor (µ/ρ) obtained as 0.026 cm2/g, 0.025 cm2/g, and 0.025 cm2/g for the Serpentine concrete as the minimum factors by MCNP5 code, WinXCOM and NXCOM software, respectively. Good agreement was seen in the results derived by the use of the applied calculation methods. Maximum values for the µ/ρ were calculated as 0.03 cm2/g, 0.029 cm2/g and 0.029 cm2/g by MCNP5 code, WinXCOM and NXCOM, respectively. For the neutron attenuation factor, calculations were conducted for the concretes and the highest and lowest ΣR/ρ were derived for Serpentine and Ordinary concretes. MCNP5 MC code was calculated ΣR/ρ for the Serpentine and Ordinary concretes as 0.039 cm2/g and 0.030 cm2/g, respectively. ΣR/ρ for the Serpentine and Ordinary concretes as 0.039 cm2/g and 0.030 cm2/g, respectively. Conclusion: It was concluded that the calculated results showed N-XCOM program can be applied for the shielding calculations for the conventional concretes studied in this work.